The Throne of the Jijats, Which Influenced the Worldview of the Jadids (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
in this article, a scientific conclusion was drawn on the basis of the coverage of the zhikats, which at the beginning of the 19th century at the beginning of the 20th century were absorbed into the worldview of the jadids, were conceived and influenced by it.